The smart city concept in Poland and Ukraine: in search of cooperation opportunities - Lozynskyy Roman; Pantyley Viktoriya; Sawicka Anna (Bulletin of Geography. Socio-Economic Series)
The article addresses the smart city concept in reference to two neigh-bouring countries – Poland and Ukraine. The paper also analyses various research trends in the scope of the smart city concept, as well as the process and conditions of the concept's implementation in the studied countries. The detailed analysis covered the implementation of the smart city concept in two cities in Poland and Ukraine belonging to neighbouring second-order administrative units, namely Lublin and Lviv. It was determined that both in Poland and Ukraine, the smart city concept is at its initial stage of implementation. This results from a number of different conditions, primarily including the socio-economic transformation of the countries, and inconsistency in reforming different spheres of socio-economic life in Ukraine. Local initiatives (analysed in detail based on the example of the cities of Lublin and Lviv) were determined to be of key importance in the implementation process.